Determination of the Binding Sites of Activators within the Proteasome Structure - Malgorzata Gizynska; Julia Witkowska; Przemyslaw Karpowicz; Fabian Henneberg; Ashwin Chari; Artur Gieldon; Elzbieta Jankowska (Proceedings, 2019)
The proteasome degrade most of the proteins in eukaryotic cells, thereby controlling the key cellular processes [...]